SOLUCIÓN NUMÉRICA DE LAS ECUACIONES DEL CAMPO DE YANG-MILLS - Villegas Silva, Fulgencio (2005)
A numerical solution of the classical field equations of the Yang-Mills theory corresponding to an infinite line of sources is presented. lt has cylindrical symmetry and is also translation invariant along the symmetry axis. The configuration presents a complete screening ofthe fields for long radial distances.